Chaplaincy and Scottish women's football: sport, gender, and pastoral care. Issue 1 (2nd January 2022) - Fleming, Mark; Parker, Andrew
ABSTRACT: As an emerging sport, élite Scottish women's football faces many of the obstacles that have traditionally blighted women's sport in general. As a result, players contend with a number of lifestyle challenges which manifest themselves in relation to issues of self-worth, self-confidence, and personal value. The present small-scale qualitative study examines the effect of these circumstances on the emotional wellbeing of female players and the way sports chaplaincy might assist in providing support within this context. Placing the personalised accounts of eight Scottish female élite footballers at the centre of the analysis, findings demonstrate that, while players generally perceived the conditions and consequences of their sporting lives as negative and discriminatory, their experiences of the pastoral care (confidential listening, affirmation, encouragement) provided by chaplains was largely positive. The article concludes by suggesting that sports chaplains can play a key role in Scottish women's football as part of wider mechanisms of player wellbeing and support.